The Algebra of Semigroups of Sets - Aigner, Mats; Chatyrko, Vitalij A.; Nyagahakwa, Venuste (Mathematica Scandinavica, 2015)
We study the algebra of semigroups of sets (i.e. families of sets closed under finite unions) and its applications. For each n > 1 we produce two finite nested families of pairwise different semigroups of sets consisting of subsets of R^n without the Baire property.